Radiopaque tissue transfer and X-ray system versus standard specimen radiography for intraoperative margin assessment in breast-conserving surgery: randomized clinical trial. Issue 4 (10th August 2022) - Stachs, Angrit; Bollmann, Julia; Martin, Annett; Stubert, Johannes; Reimer, Toralf; Gerber, Bernd; Hartmann, Steffi
Abstract: Background: Reduction of positive margin rate (PMR) in breast-conserving surgery (BCS) of non-palpable breast cancer remains a challenge. The efficacy of intraoperative specimen radiography (SR) is unclear. This randomized trial evaluated whether the PMR was reduced by the use of devices that allow precise localization of the affected margins. Methods: Patients with microcalcification-associated breast cancer undergoing planned BCS were enrolled. Study participants were randomized to receive either SR with radiopaque tissue transfer and X-ray system (KliniTray TM ) or the institutional standard procedure (ISO). In all patients with a radiological margin less than 5 mm, an immediate re-excision was conducted. The primary outcome was the PMR. Risk factors for positive margins and the effect of immediate re-excision on final surgery were secondary analyses. Results: Among 122 randomized patients, 5 patients were excluded due to the extent of primary surgery and 117 were available for analysis. Final histopathology revealed a PMR of 31.7 per cent for the KliniTray TM group and 26.3 per cent for the ISO group ( P = 0.127). Independent factors for positive margins were histological tumour size more than 30 mm (adjusted OR (aOR) 10.73; 95 per cent c.i. 3.14 to 36.75; P < 0.001) and specimen size more than 50 mm (aOR 6.65; 95 per cent c.i. 2.00 to 22.08; P = 0.002). Immediate re-excision due to positive SR led to an absolute risk reduction in positive margins of 13.6 per cent (from 42.7 to 29.1 per cent). Conclusion: Specimen orientation with a radiopaque tissue transfer and X-ray system did not decrease the PMR in patients with microcalcification-associated breast cancer; however, SR and immediate re-excision proved to be helpful in the reduction of PMR. Registration number: DRKS00011527 (https://www.drks.de ). Abstract : This prospective randomized study aimed to answer the question of whether in patients with breast-conserving surgery (BCS) of ductal carcinoma in situ (DCIS), the need for a second surgery due to affected margins can be reduced with a radiopaque tissue transfer and X-ray system (KliniTray TM ) for intraoperative specimen radiography. No significant difference was found between specimen radiography with the KliniTray TM system versus institutional standard orientation; however, specimen radiography followed by immediate re-excision led in 32 per cent of cases to conversion from initially positive to finally negative pathological margins in BCS of predominantly intraductal breast cancer associated with microcalcifications. Based on these findings, specimen radiography is of limited use to reduce the positive margin rate in BCS of DCIS independently of the technique for specimen orientation.